2002
DOI: 10.1046/j.1523-1755.2002.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory interleukin-10 genotype protects dialysis patients from cardiovascular events

Abstract: The IL-10 genotype influences the risk for cardiovascular events in hemodialysis patients and allows the definition of a high risk group. The data provide further evidence for a causal role of systemic inflammation for progressive atherosclerosis in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 20 publications
4
64
0
1
Order By: Relevance
“…IL-6 is appreciated to act more systemically and thus may more accurately reflect circulating levels; however, adipose tissue may contribute a considerable amount of systemic IL-6 and may not completely reflect response to inflammation. 55,56 While we attempted to select prototypical pro-and anti-inflammatory cytokines most relevant to renal abnormality for our study, we ultimately examined only one proinflammatory and one anti-inflammatory biomarker; other investigators have assessed larger panels. Our group traditionally examines biomarkers in relevant pathophysiologic panels and plans to further explore other inflammatory markers in future studies.…”
Section: J Am Soc Nephrol 26: 3123-3132 2015mentioning
confidence: 99%
“…IL-6 is appreciated to act more systemically and thus may more accurately reflect circulating levels; however, adipose tissue may contribute a considerable amount of systemic IL-6 and may not completely reflect response to inflammation. 55,56 While we attempted to select prototypical pro-and anti-inflammatory cytokines most relevant to renal abnormality for our study, we ultimately examined only one proinflammatory and one anti-inflammatory biomarker; other investigators have assessed larger panels. Our group traditionally examines biomarkers in relevant pathophysiologic panels and plans to further explore other inflammatory markers in future studies.…”
Section: J Am Soc Nephrol 26: 3123-3132 2015mentioning
confidence: 99%
“…Furthermore, it has been suggested that IL-10 kinetics are different in CKD patients (4). An earlier study showed large interindividual differences in serum IL-10 levels in patients undergoing hemodialysis caused by promoter gene polymorphism (8).…”
Section: Introductionmentioning
confidence: 98%
“…Although Heeschen et al (6) found that higher serum IL-10 levels were related to better clinical outcomes in terms of CV morbidity and mortality among patients with acute coronary syndrome (ACS), Mälarstig et al (7) showed the opposite. Several potential explanations for this discordance have been suggested (8,9). Furthermore, it has been suggested that IL-10 kinetics are different in CKD patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…High and low IL-10 producers can be distinguished genetically by single nucleotide polymorphisms (SNPs) in the promoter region of the IL-10 gene [23]. In dialysis patients low IL-10 production is associated with increased levels of C-reactive protein [24]. Moreover, a diminished vaccination response against hepatitis B is generally found in low IL-10 producers, and cardiovascular complications occurs significantly more often in this group of dialysis patients.…”
Section: Introductionmentioning
confidence: 99%